Preoperative Immunonutrition and Postoperative Outcomes in Radical Pancr eatic oduod enect omy Patients - Aba, Murat; Sarıtaş, Ahmet Gökhan; Yavuz, Burak; Dalcı, Kubilay; Ülkü, Abdullah; Akçam, Atılgan Tolga (Turkish Journal of Gastroenterology, 2023)
Background/Aims: This study aimed to compare the patient groups who received and did not receive immunonutrition in terms of mor tality and morbidity in patients who underwent radical pancr eatic oduod enect omy. Materials and Methods: Two groups were formed from 40 patients who underwent radical pancr eatic oduod enect omy in our clinic in 2021. The patients in study group were given enteral immunonutrition support for 5 days preoperatively. For this purpose, a standard enteral immunonutrition product containing arginine, omega-3 fatty acids, and RNA (dietary nucleotides) was used. Patients’ data of demographical, laboratory, postoperative complications, and current clinical status were analyzed. Result: Mortality developed in 5 (25 %) patients in the treatment group and 4 (20 %) patients in the control group in the following months (P > .05). The estimated survival rate in the treatment group was 21.8 ± 2.8 months in the treatment group 19.1 ± 1.7 months in the control group (P > .05). The length of hospital stay was 12.89 ± 3.3 days in the treatment group, while it was 16.47 ± 6.83 days in the control group (P < .05). In the postoperative follow-ups, delayed gastric emptying symptoms developed in 3 patients in the treat ment group, while the same complication was observed in 9 patients in the control group (P < .05). Surgical site infections occurred in 4 patients in the treatment group and 9 patients in the control group (P < .05). Conclusion: It was observed that preoperative oral immunonutrition before pancr eatic oduod enect omy was effective in reducing the risk of delayed gastric emptying after surgery and the length of hospital stay. Cite this article as: Aba M, Sarıtaş AG, Yavuz B, Dalcı K, Ülkü A, Akçam AT. Preoperative immunonutrition and postoperative outcomes in radical pancr eatic oduod enect omy patients. Turk J Gastroenterol. 2024;35(1):32-40.